Anatomical and functional visual network patterns in progressive multiple sclerosis. Issue 5 (20th December 2021) - Backner, Yael; Zamir, Sol; Petrou, Panayiota; Paul, Friedemann; Karussis, Dimitrios; Levin, Netta
Abstract: The gradual accrual of disability over time in progressive multiple sclerosis is believed to be driven by widespread degeneration. Yet another facet of the problem may reside in the loss of the brain's ability to adapt to the damage incurred as the disease progresses. In this study, we attempted to examine whether changes associated with optic neuritis in the structural and functional visual networks can still be discerned in progressive patients even years after the acute insult. Forty‐eight progressive multiple sclerosis patients, 21 with and 27 without prior optic neuritis, underwent structural and functional MRI, including DTI and resting state fMRI. Anatomical and functional visual networks were analyzed using graph theory‐based methods. While no functional metrics were significantly different between the two groups, anatomical global efficiency and density were significantly lower in the optic neuritis group, despite no significant difference in lesion load between the groups. We conclude that long‐standing distal damage to the optic nerve causes trans‐synaptic effects and the early ability of the cortex to adapt may be altered, or possibly nullified. We suggest that this limited ability of the brain to compensate should be considered when attempting to explain the accumulation of disability in progressive multiple sclerosis patients. Abstract : We attempted to examine whether changes associated with optic neuritis can still be discerned in progressive multiple sclerosis patients, even years after the acute insult. To that end we used DTI and resting state fMRI to delineate anatomical and functional visual networks, in progressive patients with or without prior optic neuritis. While no functional metrics were significantly different between the two groups, the integrity of the visual anatomical networks was significantly lower in the optic neuritis group. Thus, we conclude that widespread degeneration is probably accompanied by a reduced brain's ability to adapt itself to the damage incurred as the disease progresses.